Perioperative Craniotomy Excision of Dextra Subtemporal Tumor with Thiopental, Sufentanyl and Invasive Monitor - Guruh Perkasa; Iwan Dwi Cahyono; Aditya Pradana Kartinofan (Jurnal Neuroanestesi Indonesia)
Intracranial masses can arise from a variety of aetiologies, including congenital, neoplastic, infectious, or vascular processes, each requiring distinct diagnostic and management considerations. Establishing the presence or absence of intracranial hypertension is a critical component of the preoperative evaluation for patients undergoing craniotomy for mass lesions. Hemodynamic is an examination of the physical aspects of blood circulation, cardiac function and physiological characteristics of peripheral vasculature. A 74 year old man was admitted to the hospital because of cephalgia, and left limb weakness. Previously, the patient often felt headaches that came and went since six months ago. Three days before being admitted, the patient felt weak in his left limb and experienced decreasing in consciousness. The patient was given thiopental because the onset of action of thiopental was very short. Administration of intravenous doses of thiopental can cause cerebral vasoconstriction. Sufentanil was administered as an analgesic, because sufentanil is an opioid that has a rapid onset and analgesic potential, compared to fentanyl, intravenous and sufentanil is 5–10 times stronger. This efficacy to maintain adequate cerebral perfusion pressure (CPP), reduce cerebral blood flow (CBF), maintain normal autoregulation, reduce cerebral metabolic rate for oxygen (CMRO2). Arterial cannulation with continuous transduction is considered the gold standard for blood pressure monitoring during anaesthetic procedures. Rapid fluctuations in blood pressure can occur due to patient positioning, surgical manipulation, and the effects of anaesthetics drugs, and close monitoring of these changes is crucial for maintaining hemodynamic stability. The impact of anaesthetic management on CBF is also an integral component of neuroanesthesia, as increases in CBF are associated with increases in cerebral blood volume (CBV). An effective neuro-anesthesia management program that incorporates both invasive blood pressure monitoring and optimization of cerebral perfusion that can help preserving hemodynamic stability and improving outcomes for patients undergoing craniotomy surgery.